Loyalitas Pelanggan Berbasis Green Brand Image dan Green Trust di I.C.O Water - Ramadan, Ach. Nur Ilham; Sa'adah, Siti (LPPM Universitas Sangga Buana, 2025)
Environmental damage caused by business activities opens up opportunities for business actors to apply the green marketing concept. Components such as green brand image and green trust are important elements of green marketing that can increase customer loyalty, along with increasing public awareness of the importance of protecting the environment. This research aims to test the significant and positive influence, both partially and simultaneously, of green brand image and green trust on I.C.O Water customer loyalty in Laok Jang-Jang Village, Arjasa District, Sumenep Regency. This research uses quantitative methods by collecting data through observation, interviews and documentation. The research population was all I.C.O Water customers, with a sample of 80 people selected using purposive sampling techniques. The sample size is determined based on the Roscoe formula because the population size is unknown. The research results show that partially, the variables Green Brand Image (X1) and Green Trust (X2) have a positive and significant influence on customer loyalty (Y), so that the first and second hypotheses are accepted. Simultaneously, all independent variables (green brand image and green trust) have a significant influence on customer loyalty, so that the fourth hypothesis is accepted. This research concludes that implementing green marketing strategies, especially through strengthening green brand image and green trust, can be a key factor in increasing I.C.O Water customer loyalty.